A Bibliometric Analysis of Digital Gold Investment in Islamic Finance: Mapping Research Trends and Future Directions - Trisna Caraka Putra Prima; Hastarini Dwi Atmanti; Indah Susilowati (Journal of Economics and Management Scienties, 2026)
Digital gold investment within the Islamic finance framework has emerged as a significant area of research, particularly as fintech disrupts traditional asset management. However, no comprehensive bibliometric study has systematically mapped the intellectual landscape of this topic. This study presents a bibliometric analysis of 1,163 publications retrieved from the Scopus database, spanning from 1987 to 2025, focusing on Islamic finance, gold investment, and digital assets. Using descriptive statistics and Lotka’s Law analysis, the study identifies publication trends, key authors, productive journals, leading countries, and prominent research themes. Results reveal a sharp increase in publications post-2019, with 2025 recording the highest output (208 documents). Malaysia and Indonesia are the most productive countries. Lotka’s Law confirms that 86.8% of authors contributed only one publication, indicating a broad yet fragmented scholarly community. Key emerging themes include Islamic fintech, blockchain-based gold, Shariah compliance frameworks, and digital asset regulation. The findings provide a roadmap for researchers, policymakers, and Islamic financial institutions to identify research gaps and guide future studies on halal digital gold investment.